Outcomes after HSCT for mucolipidosis II (I-cell disease) caused by novel compound heterozygous GNPTAB mutations - He, Si-jia; Li, Dong-jun; Lv, Wen-qiong; Tang, Wen-hao; Sun, Shu-wen; Zhu, Yi-ping; Liu, Ying; Wu, Jin; Lu, Xiao-xi (Frontiers in Pediatrics, 2023)
Background: Mucolipidosis type II (MLII), or I-cell disease, is a rare lysosomal storage disease (LSD) caused by variants in the GNPTAB gene. MLII patients exhibit clinical phenotypes in the prenatal or neonatal stage, such as marked dysmorphic features, cardiac involvement, respiratory symptoms, dysostosis multiplex, severe growth abnormalities, and mental and motor developmental abnormalities. The median age at diagnosis for MLII is 0.7 years, the median survival is 5.0 years, and the median age at death is 1.8 years. No cure for MLII exists. Methods: Sanger sequencing of the GNPTAB gene identified the compound heterozygous mutations c.673C>T in exon 7 and c.1090C>T in exon 9, which were novel double heterozygous mutations first reported in China. For the first time, we describe our experience in the use of HSCT for MLII. Our patient underwent HSCT with cells from a 9/10 human leukocyte antigen (HLA)-matched unrelated donor at 12 months of age. Myeloid neutrophil and platelet engraftment occurred on Days 10 and 11, respectively. Results: The patient's limb muscle tension was significantly reduced, and his gross and fine motor skills were improved four months after transplantation. DST(Developmental Screen Test) results showed that the patient's fine motor skills and mental development were improved compared with before HSCT. Conclusion: MLII is a very severe lysosomal storage disease, to date, only 3 cases have been reported on the use of HSCT to treat MLII. Our data show that HSCT is a potential way to prolong the life of patients and improve their quality of life. Due to the lack of comparable data and time, the exact benefit remains unclear in MLII patients. Longer-term follow-up and in-depth prospective studies are indispensable.